Konsep Riba dalam Transaksi Shopee Paylater - Eko Andri; Ulya Hijrianti; Vinkan Kusdwiharyani; Muhammad Zaki; Mabruri Mabruri (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the transaction mechanism of Shopee PayLater, understand the concept of riba in islamic economics, identify riba elements in Shopee PayLater, and examine the perspective of syaria fatwas and regulations on the service. The method used is library research with a normative approach. Data were collected from scientific journals, books, DSN-MUI fatwas, and OJK offisial documents, then analyzed  using content analysis. The results show that the Shopee PayLater mechanims applies a service fee of 2,95% per month, a heandling fee of 1% and a late penalty of 5%, which contain elements of riba al-qardh and riba al-jahiliyyah. In addition, theree is an element of gharar due to unclear information on penalties. DSN-MUI fatwa  No. .116/DSN-MUI/IX/2017 recognizes the qardh contract in sharia electronic money, but fatwa No. 19/DSN-MUI/IV/2001 emphasizes that and additional fee stipulated at the beginning of the conctract constitutes riba and is haram.. from a regulatory perspective, OJK throught SLIK records defaulting users as blacklisted, preventing them from accessing other loans. The implication of this research provides a comprehensive understanding that Shopee PayLater does not comply with sharia princiiples due to the presence of riba and gharar.